Kedudukan Peradilan Tata Usaha Negara dalam Penyelesaian Sengketa Aparatur Sipil Negara di Indonesia - Subri Subri; Aqilah Dzakirah; Olga Arawinda Nasiswa; Anisya Nurroliyati Rahmadina; Madinar Madinar (AHKAM, 2026)
The State Administrative Court (PTUN) plays a central role as an instrument of judicial oversight of personnel administrative decisions that may harm State Civil Apparatus (ASN). This study aims to analyze the mechanism for resolving ASN personnel disputes through the PTUN from the aspects of authority, procedure, and the substance of personnel administrative decisions, as well as to examine forms of legal protection for ASN who are harmed by decisions of dishonorable dismissal. This study used a normative legal method with a statutory approach and a case approach, referring to Jakarta State Administrative Court Decision Number 170/G/2020/PTUN.Jkt as the main analytical material. The results show that the mechanism for resolving ASN personnel disputes through the PTUN is systematic and multilayered. ASN are first required to pursue administrative remedies in the form of objections and administrative appeals before filing a lawsuit with the PTUN, which subsequently examines the validity of the State Administrative Decision based on authority, procedure, and its conformity with the General Principles of Good Governance. Legal protection for ASN subjected to dishonorable dismissal is realized through two dimensions, namely preventive protection in the form of guarantees of a fair examination process and the right to defend oneself, and repressive protection in the form of the right to pursue the state administrative court mechanism accompanied by the right to rehabilitation if the lawsuit is granted. The conclusion of this study emphasizes that the PTUN has an important position in ensuring legal certainty, procedural justice, and the protection of ASN rights in personnel administrative disputes. The implications of the study show that the effectiveness of legal protection for ASN greatly depends on the quality of evidence and procedural compliance from the early stages of the personnel process.